A MELTING POT OF MALANG: LINGUISTICS LANDSCAPE OF MALANG CULINARY SIGNS - Milania Fitri Iwana; Emy Sudarwati (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2021)
There are numerous studies of linguistics landscape or study of texts in public spaces. However, study on the culinary sign is still rare in Indonesia. Thus, this paper explores the linguistics landscape of culinary signs around campus in Malang, East Java, Indonesia, the melting pot of cultures and languages. The research aims to analyze the form of language use and its function. The data collection is photographing culinary signs around three advanced campuses in Malang, namely the University of Brawijaya, State University of Malang, and the University of Muhammadiyah Malang. Qualitative descriptive was used in analyzing the data. The results showed that Indonesian, English, and Javanese are the most frequent languages used in culinary banners or storefronts and other foreign languages (Japanese, Korean, Arabic, Malay) and vernaculars (Sundanese, Banjarese, Minangnese). It was found that the Malang culinary linguistics mirrored the taste and service of the store. Furthermore, foreign languages are becoming a way to go global and known by college students who most like modernization. The use of Javanese also acts as a symbol of maintaining the cultural heritage of Javanese people.